The (Hybrid) Sportsman - Mangano, Dario (E|C, 2023)
When, on December 14, 2020, Apple introduced a small application called Apple Fitness+ something more happened than simply adding one piece of software to the many that the computer giant has created: a discursive configuration was completed that redefined a subjectivity. That of the contemporary sportsman. A perfect example of a hybrid that, by holding together humans, physical objects and the software that controls them, not only acquires unprecedented capabilities, but establishes a new subjectivity. What we will do in this essay is to reconstruct through semiotics precisely that subjectivity, questioning the society that more or less voluntarily produced it and will have to deal with it in the future.